Enabling remote quantum emission in 2D semiconductors via porous metallic networks - Jose J. Fonseca; Andrew L. Yeats; Brandon Blue; Maxim K. Zalalutdinov; Todd Brintlinger; Blake S. Simpkins; Daniel C. Ratchford; James C. Culbertson; Joel Q. Grim; Samuel G. Carter; Masa Ishigami; Rhonda M. Stroud; et al. (Nature Communications, 2020)
Here, the authors develop a reverse epitaxial process whereby a nanocrystalline Au film becomes highly textured and support a suspended 2D WSe2 overlayer. Surface plasmon polaritons are launched in nanostructured Au by laser excitation and couple remotely to single photon emitters present in WSe2.